THE IDEAL LEGAL REGULATION FOR DECENTRALIZED FINANCE AS THE DEVELOPMENT OF INDONESIA CRYPTO ASSET TRADING - Bustomi, Yazid; Muryanto, Yudho Taruno (UNISSULA, 2022)
Decentralized Finance (DeFI) has positively impacted the development of crypto asset trading and has been adopted by various countries except for Indonesia. This study aims to identify the urgency of regulating DeFi as the development of crypto asset trading in Indonesia and construct the ideal regulation. This research is normative legal research with a statutory and conceptual approach. The research results stated the urgency of regulating DeFi as the development of crypto asset trading is: a) other countries have used DeFi because it can develop crypto asset trading for the better by creating value stability in crypto assets, having a function for lending and borrowing crypto assets, having transparency in transactions and lower crypto asset trading fees; b) DeFi technology adopted in the development of the Digital Rupiah project by BI and adopted by physical traders of crypto assets in Indonesia; c) as a form of legal protection from risks arising from technical or non-technical negligence or intention to protection from crime. Ideal legal regulation for decentralized finance as the development of Indonesia crypto asset trading is the formation of a regulation by CoFTRA in the form of technical guidelines and implementation mechanisms, in the form of a new written CoFTRA Regulation, in the form of a decree from the Head of CoFTRA whose focus is to regulate DeFi as development Crypto asset trading.